2016
DOI: 10.1073/pnas.1517451113
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain auditory selectivity to natural sounds

Abstract: This study investigated auditory stimulus selectivity in the midbrain superior colliculus (SC) of the echolocating bat, an animal that relies on hearing to guide its orienting behaviors. Multichannel, singleunit recordings were taken across laminae of the midbrain SC of the awake, passively listening big brown bat, Eptesicus fuscus. Speciesspecific frequency-modulated (FM) echolocation sound sequences with dynamic spectrotemporal features served as acoustic stimuli along with artificial sound sequences matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…5 ). In agreement with our results, numerous studies have reported that subcortical neurons sharpen their neuronal tuning with increasing repetition rates [IC: Myotis lucifugus ( Friend et al, 1966 ; Galazyuk et al, 2000 ), E. fuscus ( Pinheiro et al, 1991 ; Chen and Jen, 1994 ; Moriyama et al, 1994 ; Wu and Jen, 1996 ; Jen and Chen, 1998 ; Jen and Zhou, 1999 ; Jen et al, 2001 ; Zhou and Jen, 2001 ; Zhou and Jen, 2002 ; Sanderson and Simmons, 2005 ; Wu and Jen, 2006 ; Zhou and Jen, 2006 ; Jen and Wu, 2008 ); superior colliculus: E. fuscus ( Valentine and Moss, 1997 ; Wohlgemuth and Moss, 2016 )]. Some studies even described repetition rate selective neurons in the IC of insectivorous bats, like E. fuscus , ( Pinheiro et al, 1991 ; Sanderson and Simmons, 2005 ) and M. lucifugus ( Condon et al, 1994 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 ). In agreement with our results, numerous studies have reported that subcortical neurons sharpen their neuronal tuning with increasing repetition rates [IC: Myotis lucifugus ( Friend et al, 1966 ; Galazyuk et al, 2000 ), E. fuscus ( Pinheiro et al, 1991 ; Chen and Jen, 1994 ; Moriyama et al, 1994 ; Wu and Jen, 1996 ; Jen and Chen, 1998 ; Jen and Zhou, 1999 ; Jen et al, 2001 ; Zhou and Jen, 2001 ; Zhou and Jen, 2002 ; Sanderson and Simmons, 2005 ; Wu and Jen, 2006 ; Zhou and Jen, 2006 ; Jen and Wu, 2008 ); superior colliculus: E. fuscus ( Valentine and Moss, 1997 ; Wohlgemuth and Moss, 2016 )]. Some studies even described repetition rate selective neurons in the IC of insectivorous bats, like E. fuscus , ( Pinheiro et al, 1991 ; Sanderson and Simmons, 2005 ) and M. lucifugus ( Condon et al, 1994 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, to understand the neuroethological roles of the auditory centers involved in processing echolocation signals, it is necessary to investigate neuronal processing with natural echolocation sequences. So far, processing of natural echolocation sequences has been characterized in the superior colliculus of the insectivorous bat Eptesicus fuscus ( Wohlgemuth and Moss, 2016 ) and in the auditory cortex (AC) of C. perspicillata ( Beetz et al, 2016a , b ). Cortical results have shown that the natural temporal context evokes neuronal suppression which results into a high neuronal selectivity to particular call echo pairs ( Beetz et al, 2016a ) or to object-specific echo information ( Beetz et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these differences, one could argue that suppression effects could be stronger when studied with natural (as opposed to seminatural) echolocation sequences. Supporting this idea, a recent electrophysiological study showed stronger selectivity to natural than to artificial echolocation streams in subcortical neurons of the big brown bat ( Eptesicus fuscus ) 49 . These results, together with ours show that the temporal context and spectrotemporal profile of the call-echo elements affect the response selectivity.…”
Section: Discussionmentioning
confidence: 88%
“…The echolocation sequence was recorded in a pendulum paradigm in which a bat was swung towards a reflective wall (Beetz et al 2016a ). Distress and echolocation sequences have been used in previous studies characterizing the bat auditory system (Beetz et al 2016a , 2017 ; Hechavarría et al 2016b ; Wohlgemuth and Moss 2016 ; Martin et al 2017 ; García-Rosales et al 2018 ; Macías et al 2018 ). To restrict the study to units that responded to the calls, we considered only those units that carried at least 1 bit/s of information (Kayser et al 2009 ) in response to at least one of the sequences studied (864 units out of 976).…”
Section: Resultsmentioning
confidence: 99%